PENGARUH KONSUMSI SAYUR JANTUNG PISANG TERHADAP KECUKUPAN ASI IBU Suharman1),Rostina2),Lolita Sary3),Susilawati4) - Suharman Suharman; Rostina Rostina; Lolita Sary; Susilawati Susilawati (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
ABSTRACT INFLUENCE OF BANANA HEART VEGETABLE CONSUMPTION ON ASI BREASTFEEDING ASI ADMINISTRATION Background By comparing 5 health centers with the lowest ASI coverage, namely Gedong Tataan Health Center 26.27%, Pedada Health Center 29.58%, Padang Cermin Health Center 33.33%, Kalirejo Health Center 36.11, and Kedondong Health Center 37.03%. The heart of a banana is a type of plant that contains laktagogum has the potential to stimulate the hormone oxytocin and prolactin such as alkaloids, polyphenols, steroids, flavonoids and other substances most effective in increasing and facilitating the production of breast milk.The purpose of the study was to know the effect of vegetable consumption of banana heart on the smooth breastfeeding of breastfeeding mothers in the Kalirejo Pesawaran Community Health Center Working Area in 2019.Methods This quantitative study used, experimental quasy method with one group pretest - posttest design approach. Population and sample were 30 people, purposive sampling sampling technique. Data analysis using univariate and bivariate, with t-test statistical test. The study was conducted for 1 week.Result Smooth breastfeeding before being given banana heart vegetables in nursing mothers in the Kalirejo Puskesmas Working Area is offered to 17 breastfeeding mothers, with a mean of 5.00, standard deviation of 0.935, error standard 0.227 and min-max 4-7. After being given a banana heart vegetable with a mean of 7.65 standard deviation of 0.606, the error standard was 0.147 and the min-max value was 7-8. The test-dependent statistical test results obtained a p-value of 0.000 (α <0.05)Conclusion there is an influence of vegetable consumption of banana heart on the adequacy of breastfeeding mothers in the Pesawaran Kalirejo Community Health Center Working Area in 2019.Suggestion It is expected that nursing mothers can use vegetable banana heart 200gr / day as a non-pharmacological alternative to facilitate milk production Keywords : Banana Heart Vegetables, Breastfeeding Sufficiency, Breastfeeding Mothers ABSTRAK Latar Belakang Dengan membandingkan 5 puskesmas dengan cakupan ASI terendah, yaitu puskesmas Gedong Tataan 26,27%, Puskesmas Pedada 29,58%, Puskesmas Padang Cermin 33,33%, Puskesmas Kalirejo 36,11, dan Puskesmas Kedondong 37,03%. Jantung pisang merupakan jenis tanaman yang mengandung laktagogum memiliki potensi dalam menstimulasi hormon oksitosin dan prolaktin seperti alkaloid, polifenol, steroid, flavonoid dan substansi lainnya paling efektif dalam meningkatkan dan memperlancar produksi ASI. Tujuan penelitian Diketahui pengaruh konsumsi sayur jantung pisang terhadap kelancaran ASI ibu menyusui di Wilayah Kerja Puskesmas Kalirejo Pesawaran Tahun 2019.Metode Jenis penelitian kuantitatif, metode quasy eksperimental dengan pendekatan one group pretest – posttest design. Populasi dan sampel sebanyak 30 orang, teknik sampling purposive sampling. Analisa data menggunakan univariat dan bivariate, dengan uji statistik t-tes. Penelitian dilakukan selama 1 minggu.Hasil Kelancaran ASI sebelum diberi sayur jantung pisang pada Ibu menyusui di Wilayah Kerja Puskesmas Kalirejo Pesawaran terhadap 17 orang ibu menyusui, dengan mean 5,00, standar deviasi 0,935, standar eror 0,227 dan nilai min-max 4-7. Setelah diberi sayur jantung pisang dengan mean 7,65 standar deviasi 0,606, standar eror 0,147 dan nilai min-max 7-8. Hasil uji statistik menggunakan tes-dependen didapat nilai p-value 0.000 (α<0.05)Kesimpulan terdapat pengaruh konsumsi sayur jantung pisang terhadap kecukupan ASI Ibu menyusui di Wilayah Kerja Puskesmas Kalirejo Pesawaran Tahun 2019.Saran diharapkan untuk ibu menyusui agar dapat memanfaatkan sayur jantung pisang 200gr/ hari sebagai alternatif non farmakologi untuk memperlancar produksi ASI Kata Kunci : Sayur Jantung Pisang, Kecukupan ASI, Ibu Menyusui